Evaluación de la actividad antiviral de la Frenatina 2.3 S frente al virus del dengue (DEN-2) usando docking molecular y otras herramientas computacionales (2021)
Dengue fever is a disease produced by the Dengue virus. This virus has four serotypes and belongs to the Flaviviridae family known as Arboviruses. This virus is transmitted by Aedes aegypti and A. albopictus mosquitoes and has a global distribution. Annually, between 280 to 520 million people are infected with this virus (WHO, 2020) and does not have a specific vaccine nor treatment medicine. Given its global public health importance, it is important to study and search for treatments that can be effective against it. Antimicrobial peptides (AMP) have attracted attention because their characteristics of inhibiting the growth of microorganisms such as bacteria, fungi, and viruses. This project studied the previously extracted AMP Frenatina 2.3 S found on the Sphaenorhynchus lacteus skin glands. this specie is distributed in the Colombian Orinoco area. F 2.3S was characterized and described by Camargo et al. (2018) and Benitez (2019) and has shown to have antimicrobial and antiviral activity...